“You must try it”: A forensic linguistics analysis of online gambling promotions in social media comment sections - Juanda, Mochammad Rizki; Sambodo, Unggul Putra; Suryatama, Kurniawan (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This study investigates the persuasive strategies employed in online gambling advertisements circulated through social media comment sections. Drawing on a dataset of 32 interactions from TikTok between 21 August and 23 September 2025, the analysis examines how language constructs trust, credibility, and manipulation. Each dataset entry includes a primary promotional comment, often framed as a testimonial of success, and at least one reply, ensuring dialogic interaction. Using a move analysis approach, the findings reveal systematic patterns of persuasion, including claims of winning, reinforcement from other users, and staged dialogue that collectively simulate authenticity. These patterned linguistic moves demonstrate that the comments are strategically orchestrated rather than spontaneous. The recurrence of testimonial chaining, where initial claims are echoed and validated by follow up comments, emerges as a key marker of deception. Engagement metrics such as likes and replies further amplify visibility, making these illicit promotions harder to detect or remove. This study highlights how forensic linguistic analysis can uncover the structural and interactive dimensions of deceptive discourse, offering insights into the mechanisms of online gambling promotion in Indonesia’s digital landscape